Positive Outcome of Heterotopic Pregnancy Following Ovulation Induction: A Rare Case Report - Jesmin, S; Akhte, N; Naha, N; Shamima, N (TAJ: Journal of Teachers Association, 2009)
We report a combined intra-uterine and ruptured tubal pregnancy following ovulation induction by clomiphene citrate (cc) and timed intercourse. The diagnosis of heterotopic pregnancy (HP) is the major problem until occurrence of tubal rupture. Because HP is a life threatening condition, the diagnosis should be made as soon as possible. In a spontaneous conception HP is a rare event. The risk of HP significantly increases after ovulation induction. Clomiphene itself should be associated with a high HP rare. We present a case with normally developing intra uterine singleton pregnancy successfully with synchronous tubal pregnancy following ovulation induction by cc. TAJ 2009; 22(1): 287-288